Transplantation and Production of OPU Derived Hanwoo IVP Embryos - Jong-In Jin; Byung-Hyun Choi; Seong-Su Kim; Hyun-Tae Jo; Du-Won Sun; Hyun-Tae Lim; Jung-Gyu Lee; Chan-Sik Min; Il-Keun Kong (The Korean Society of Animal Reproduction and Biotechnology, 2014)
This study was carried out to establish the system of OPU derived embryo production, management of recipients as well as offspring production. OPU derived embryo production system was carried out of aspiration of immature oocytes 2 times per week, total 24 times for 3 months by an ultrasonographic guided follicular aspiration system and then produced in vitro-produced blastocysts by in vitro maturation, fertilization and culture system. This work was collected total 13,866 oocytes, average 8.2 ± 4.5 oocytes per session and 8,170 G1 + G2 grade oocytes, average 4.8 oocytes per session by 1,692 times session of total 71 donors for 4 years from 2010 to 2013. The rate of cleavage and blastocyst developmental competence were obtained 11,825 (85.3%) and 5,032 (36.3%) that was 7.0 ± 3.8 cleaved embryos and 3.0 ± 2.5 blastocysts per session. OPU derived embryo transfer were taken place in 2, 4, 6 and 7 local governments at 2010, 2011, 2012 and 2013 for 4 years and pregnancy rate were obtained 41.2, 43.9, 46.5 and 49.7% in each years. It means that pregnancy rate was continuously improved according of every year for 4 years. Pregnancy rate was significantly different according to individual local government in which was 62.7% in B, but 24.2% in F at 2012. Paternity identification was carried out total 26 offspring in C local government of 2012 and then confirmed 100% agreement of its analysis. In conclusion, the results obtained the possibility of mass production of elite cow embryos as well as offspring by OPU derived embryo production system, of which could be decreased the required time of genetic improvement.